2008
DOI: 10.1300/j069v27n02_02
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognition in Individuals Co-Infected with HIV and Hepatitis C

Abstract: Due to similar routes of viral transmission, many individuals infected with the human immunodeficiency virus (HIV) are also infected with the hepatitis C virus (HCV). Each virus can cause cognitive compromise among mono-infected individuals; evidence is accumulating that HIV/ HCV co-infection may have a particularly deleterious impact on cognition. We present neuropsychological data obtained from 118 HIV+ adults with advanced HIV disease, 35 of whom were co-infected with HCV, who completed a comprehensive neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 25 publications
4
58
3
2
Order By: Relevance
“…In fact, the new conceptual model of aging with HIV infection proposed by the HIV and Aging Working Group of the NIH Office of AIDS Research posits that medical co-morbidities are seen earlier and more frequently in older PLWH, which leads to frailty, neurocognitive and functional impairment, organ system failure, and increased hospitalization. 11 Across the lifespan, HIV is associated with increased rates of co-morbidities such as hepatitis C co-infection 12 and metabolic syndrome 13 that heighten risks of adverse cognitive 13,14 and health-related outcomes (e.g., chronic liver disease progression 12 ). As PLWH grow older, they also become more susceptible to developing the physical and mental diseases associated with so-called ''normal'' aging.…”
mentioning
confidence: 99%
“…In fact, the new conceptual model of aging with HIV infection proposed by the HIV and Aging Working Group of the NIH Office of AIDS Research posits that medical co-morbidities are seen earlier and more frequently in older PLWH, which leads to frailty, neurocognitive and functional impairment, organ system failure, and increased hospitalization. 11 Across the lifespan, HIV is associated with increased rates of co-morbidities such as hepatitis C co-infection 12 and metabolic syndrome 13 that heighten risks of adverse cognitive 13,14 and health-related outcomes (e.g., chronic liver disease progression 12 ). As PLWH grow older, they also become more susceptible to developing the physical and mental diseases associated with so-called ''normal'' aging.…”
mentioning
confidence: 99%
“…According to these results, coexistence of HCV may be connected with the overall slowing of mental processes. Hinkin et al came to a similar conclusion [20]. The authors investigated 118 individuals, among whom 35 were also infected with HCV, using a comprehensive test battery measuring abstraction and executive functions, information processing, attention, learning, memory, verbal fluency, motor functions and global cognitive function.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, it can be assumed that HIV/HCV co-infected patients were in an overall worse medical condition, taking into account that 25 of them were in advanced stages of AIDS, while in the group of mono HIV-infected patients only 10 met these criteria. Moreover, as other authors who had not included patients with clinical diagnoses of hepatic encephalopathy to the study, we cannot exclude that some of the individuals might have had it at slight or sub-clinical level [20].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, several demographic and HIV-related factors have been associated with neurocognitive impairment. These include: older age (Fazeli et al, 2011;Lopardo et al, 2009;4 Richarson et al, 2002), lower education (De Ronchi et al, 2002;Tozzi et al, 2007;Waldrop-Valverde et al, 2010), professional situation (Heaton et al, 2011;Woods et al, 2011), ethnicity (Durvasula et al, 2001;Manly et al, 2011), and HIV/HCV co-infection (Hinkin et al, 2008;Richardson et al, 2005). Although inconsistent, some studies have also found an association between neurocognitive impairment and lower CD4 count (De Ronchi et al, 2002;Fazeli et al, 2011;Njamnshi et al, 2009;Osowiecki et al, 2000), and higher plasma viral load (Marcotte et al, 2003;Tate et al, 2011).…”
Section: Introductionmentioning
confidence: 99%